Maqashid Al Shariah in Economic Development: Theoretical Review of Muhammad Umer Chapra's Thoughts - Kusnan; Muhammad Damar Hulan bin Osman; Khalilurrahman (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
Muhammad Umer Chapra is among leading experts in Islamic economics. He published many well-known books, such as The Future of Economics: An Islamic Perspective, which reconstructed Ibn Khaldun's classical thinking and aimed to direct how the economic development of a country should be carried out. He also published a research paper entitled â€œThe Islamic Vision of Development in the Light of MaqÄá¹£id Al-SharÄ«áº£hâ€ as formulation on how to implement goals of shariah in economic development or maqashid al shariah. Muamalah activities, such as economic development, cannot be separated from the context of maqashid al shariah. This study aims to analyze whether the theory constructed by Chapra follows the principles of maqashid al shariah as proposed by other Muslim scholars: Al-Shatibi and Jasser Auda. Furthermore, it also analyzes Chapraâ€™s thoughts with correspondence to five fiqh legal maxims or qawaidh fiqhiyah. This study applied traditional or narrative review as a method of analysis. The results show that Chapraâ€™s thoughts aligned with maqashid al shariah as proposed by Al-Shatibi and Jasser Auda and with the five fiqh legal maxims.